Quality of life in patients with pulmonary embolism treated with edoxaban versus warfarin. Issue 5 (14th July 2021) - Bavalia, Roisin; Bistervels, Ingrid M.; Boersma, Wim G.; Quere, Isabelle; Brisot, Dominique; Falvo, Nicolas; Stephan, Dominique; Couturaud, Francis; Schellong, Sebastian; Beyer‐Westendorf, Jan; Montaclair, Karine; Ghanima, Waleed; et al.
Abstract: Background: Long‐term sequelae of acute pulmonary embolism (PE) include decreased quality of life (QoL). Evidence suggests that adequacy of initial anticoagulant treatment in the acute phase of venous thrombosis has a key impact on late postthrombotic complications. We hypothesize that patients with acute PE treated with edoxaban for acute PE experience have improved QoL compared to those treated with warfarin. Methods: Patients with PE who participated in the Hokusai‐VTE trial were contacted between June 2017 and September 2020 for a single long‐term follow‐up visit. Main outcomes were the generic and disease‐specific QoL measured by the 36‐Item Short Form Health Survey (SF‐36) and Pulmonary Embolism Quality of Life questionnaire. Results: We included 251 patients from 26 centers in eight countries, of which 129 (51%) had been assigned to edoxaban and 122 (49%) to warfarin. Patient‐ and thrombus‐specific characteristics were similar in both groups. Mean time since randomization in the Hokusai‐VTE trial was 7.0 years (standard deviation, 1.0). No relevant or statistical differences were observed in the QoL for patients treated with edoxaban compared to patients treated with warfarin. The mean difference between patients treated with edoxaban and patients with PE treated with warfarin was 0.8 (95% confidence interval [CI]. −1.6 to 3.2) for the SF‐36 summary mental score and 1.6 (95% CI, −0.9 to 4.1) for summary physical score. Conclusion: Our findings indicate that patients with an index PE treated with edoxaban or warfarin have a similar long‐term QoL. Since our study was a follow‐up study from a well‐controlled clinical trial setting, future studies should be designed in a daily clinical practice setting. We suggest a longitudinal design for investigation of changes in QoL over time.